The Role of Academic Buoyancy and Social Support on English as a Foreign Language Learners’ Motivation in Higher Education - Jia, Yanxian; Cheng, Ling (Frontiers in Psychology, 2022)
Since motivation determines progress in the class, it has a significant role in the field of learning English as a foreign language (EFL), contributing to a successful learning process. Therefore, teachers need to motivate learners to achieve their learning goals and provide them with a meaningful learning process in stressful situations. Two factors are required to successfully overcome challenges in scholastic circumstances such as academic buoyancy and social support. The former can be a significant element in a psycho-educational setting that helps learners with academic difficulties and the latter is another term that is deemed as an important predictor of academic motivation even when considering perceived support from teachers and peers. The functions of academic buoyancy and social support factors in the process of learning and their association with students’ motivation have not been taken into account so far. As a result, this review has implications for scholars, theorists, and practitioners in quest of better investigating and addressing the roles of buoyancy and social support on students’ motivation.